Towards a new model for the calculation of CPVC in latex coatings (2015)
It has been shown graphically that the monodisperse resins give rise to higher LCPVC values than polydispersed resins, which ultimately allows the coatings formulator to propose latex paints with higher PVCs and therefore coatings with a better cost/benefit relationship. The LCPVC model is a function of the particle size ratio between the resin and the pigmentary system, so the equation which has been derived in the work is not a function of any OAI value of the pigmentary system. There is a relatively successful model to calculate the CPVC (critical pigment volume concentration) in solvent-based paints as a function of the OAI, but there is no similar successful one for latex paints, reflecting the deep physical-chemical differences between both coating systems. Previous models proposed for latex systems may be considered unreliable because they are proposed as a function of the OAI, while this model can better represent the particles' condition (pigment as much as resin) at the LCPVC, although it could be subject to some future refinements.